2021
DOI: 10.3389/fmolb.2021.681526
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Biomarkers and Immune Infiltration in Systemic Juvenile Idiopathic Arthritis by Integrated Bioinformatic Analysis

Abstract: Systemic juvenile idiopathic arthritis (sJIA) is a rare and serious type of JIA characterized by an unknown etiology and atypical manifestations in the early stage, and early diagnosis and effective treatment are needed. We aimed to identify diagnostic biomarkers, immune cells and pathways involved in sJIA pathogenesis as well as potential treatment targets. The GSE17590, GSE80060, and GSE112057 gene expression profiles from the Gene Expression Omnibus (GEO) database were screened to obtain differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The pathway has been found to participate in insulin-resistant, hypothalamic signaling associated with diabetes remission, the regulatory mechanism associated with diabetic nephropathy, etc [33][34][35]. On the other hand, MAPK-ERK pathway mediating the abnormal activation of broblast-like synoviocytes is believed to be involved in the joint destruction process in rheumatoid arthritis, and the increasing evidence of MAPK involvement in sJIA is gradually being discovered, but the underline mechanism is still needed to be further explored [36,37]. JAK-STAT is an evolutionarily conserved signaling pathway mediating cellular responses to cytokines and growth factors, mediating cell proliferation, differentiation, migration, apoptosis, and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway has been found to participate in insulin-resistant, hypothalamic signaling associated with diabetes remission, the regulatory mechanism associated with diabetic nephropathy, etc [33][34][35]. On the other hand, MAPK-ERK pathway mediating the abnormal activation of broblast-like synoviocytes is believed to be involved in the joint destruction process in rheumatoid arthritis, and the increasing evidence of MAPK involvement in sJIA is gradually being discovered, but the underline mechanism is still needed to be further explored [36,37]. JAK-STAT is an evolutionarily conserved signaling pathway mediating cellular responses to cytokines and growth factors, mediating cell proliferation, differentiation, migration, apoptosis, and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Six hub genes were identified, three of which had high diagnostic sensitivity and specificity; ARG1 and PGLYRP1 were validated by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and microarray data from the GSE8361 dataset as potential markers for the early diagnosis of JIA, revealing new pathways and molecular targets for sJIA. Further studies with larger sample sizes and in-depth analysis are needed to confirm these results [ 28 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%
“…The important roles of platelets and the MAPK pathway in the pathogenesis of sJIA provide a new perspective for exploring potential molecular targets for the treatment of sJIA, as Zhang et al revealed by integrated bioinformatics analysis [ 28 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%